ORGANOLEPTIC ANTIOXIDANT ACTIVITY, AND VITAMIN C ANALYSIS ON JAMBLANG (Syzygium cumini L.) SEEDS COFFEE - Fitri Komala Sari; Putri Verrany Dheasandra; Lulu’ Luthfiya; Nur Aini Mahmudah; Sofiatun Annayah; Ashifa Purnama Putri (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2023)
One of Indonesia's natural resources, jamblang (Syzygium cumini L.) seed, which is a byproduct of jamblang fruit, contains antioxidants and can be used to make jamblang seed coffee. With a fully randomized design, the aim of this study was to evaluate the level of liking, antioxidant activity, and vitamin C in jamblang seed coffee (RAL). Data that has been collected, statistically tested using Duncan's Multiple Range Test (DMRT). The two degrees of treatment in this study are roasting jamblang seeds for either 10 or 20 minutes, with robusta coffee serving as the control. Various roasting times of jamblang coffee beans result in different antioxidant and vitamin C levels jamblang coffee beans cooked for 10 minutes have higher levels of both.